Discrete element modeling of masonry structures: Validation and application - Pulatsu, Bora (2016)
The failure mechanism and maximum collapse load of masonry structures may change significantly under static and dynamic excitations depending on their internal arrangement and material properties. Hence, it is important to understand correctly the nonlinear behavior of masonry structures in order to adequately assess their safety and propose efficient strengthening measures, especially for historical constructions. The discrete element method (DEM) can play an important role in these studies. This paper discusses possible collapse mechanisms and provides a set of parametric analyses by considering the influence of material properties and cross section morphologies on the out of plane strength of masonry walls. Detailed modeling of masonry structures may affect their mechanical strength and displacement capacity. In particular, the structural behavior of stacked and rubble masonry walls, portal frames, simple combinations of masonry piers and arches, and a real structure is discussed using DEM. It is further demonstrated that this structural analysis tool allows obtaining excellent results in the description of the nonlinear behavior of masonry structures.